Examining the Impacts of Environmental Characteristics on Shariah-Based Bank’s Capital Holdings: Role of Country Risk and Governance Quality - Athari, Seyed Alireza (The Economics and Finance Letters, 2022)
This study investigates the effects of environmental characteristics, namely the quality of country-level governance and domestic risk on Islamic banking capital decisions. To do so, this study selects 29 listed Islamic banks operating in Arab markets for the wide range between the 2003-2018 period by performing the System-GMM dynamic panel technique. The results underscore that higher country-level governance quality is linked with higher capital ratios and Islamic banks increase capital ratios specifically by improving methods of anti-corruption, political stability, government effectiveness, and legal systems. Moreover, the results reveal that Islamic banks increase capital ratios by the rise of a country’s vulnerability, particularly by increasing financial and economic risks. However, the results suggest that decreasing political risk also corresponds with higher capital ratios. Overall, the results confirm that environmental characteristics have a pivotal role in determining Islamic bank capital ratios. The results are robust and the findings of this study are likely to open new discussions in the banking literature.